ANALISIS PERTUMBUHAN AKAR DAN FASE MITOSIS BAWANG MERAH DENGAN PERLAKUAN AIR BIASA, MSG, TEH - Silvani Elisabet Nainggolan; Talitha Arisanti; Fira Khairun Niswah; Larasati Arum Utami (Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2026)
This study aimed to analyze the effects of plain water, MSG solution, and tea solution on root growth and mitotic phases in the root meristem cells of shallot (Allium cepa L.). this research was conducted experimentally using a completely randomized design with three treatments and two replications. Shallot bulbs were soaked for 48 hours in each treatments solution, and the grown roots were measured and prepared for microscopic observation using the squash method with acetocarmine staining. The data were analyzed descriptively based on root growth, observed mitotic index values. The results showed that the tea solution treatment produced the highest root growth, with an average root length of 1,5 cm and a mitotic index of 15.42%. The MSG solution treatment produced an average root length of 0,40 cm and a mitotic index of 4,59%, while the plain water treatment produced an average root length of 0,15 cm with a mitotic index of 0%. Microscopic observations showed that the MSG and tea treatments had reached the prophase stage, whereas the plain water treatment remained in interphase. These results indicate that tea solution was more effective in stimulating root growth and meristematic cell division activity in shallot compared to MSG solution and plain water.